Game Concept for Seual Child Abuse Anticipation - Fajar As'ari; Ridwan Sanjaya; Hendra Prasetya (SISFORMA, 2016)
Sexual child abuse are direct or indirect action from people who is older than children are. People whose close and known by children 90% of them are being sexual child abuse offenders. Sexual child abuse preventive measure delivered through sexual education by media such as pictures, comic, and video. Create this media as a tool to guide parents to teach their children to keep them safe from child sexual abuse.Parents could choose video that provide animation with stories detailing and watching together with their child, or accompany children and tells story through comic and spending time together. Alternatively, by playing education game, children play it and parent accompany them, explain the story in the game, and enjoy the animation on the game.This research will discuss about drafting a game as a media to prevent sexual child abuse. Formulate appropriates story for children and information that will be presented in the game. Reviewing literature and media that already exist about sexual child abuse and the way to prevent it are materials gathering process. Discussion also has done with psychologist and childrens sex education expert to confirm literature review results, also to formulate games for children.